1996
DOI: 10.1177/108201329600200601
|View full text |Cite
|
Sign up to set email alerts
|

Review: Biochemical and technological assessment of the metabolism of pure and mixed cultures of yeast and lactic acid bacteria in breadmaking applications / Revisión: Aspectos bioquímicos y tecnológicos del metabolismo de cultivos puros y mixtos de levaduras y bacterias ácido lácticas en panificación

Abstract: The production of varieties of breads with the quality required at present by the European consumer closely relates to the proper use of starting microorganisms in controlled and optimized breadmaking conditions. The relationship between processing requirements and wheat bread quality involves an understanding of the metabolism of the starting microflora which regulate production or assimilation of suitable and unsuitable metabolites during the breadmaking process, mediated by the specific enzyme activities an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(12 citation statements)
references
References 27 publications
1
9
1
1
Order By: Relevance
“…This indicates that bread made from rice bran sourdough with high to moderate acid content will have better textural properties. The trend of lactic acid values recorded for rice bran sourdough in this study was incongruent with that of Collar (1996).…”
Section: Organic Acids Ethanol and Sugar Contents Of The Rice Bran Scontrasting
confidence: 70%
“…This indicates that bread made from rice bran sourdough with high to moderate acid content will have better textural properties. The trend of lactic acid values recorded for rice bran sourdough in this study was incongruent with that of Collar (1996).…”
Section: Organic Acids Ethanol and Sugar Contents Of The Rice Bran Scontrasting
confidence: 70%
“…If looking at the values obtained within one type of inoculum, significantly higher values were detected in samples produced at 35 °C, which was especially denoted in sample 0:100 containing only kefir grains. Since ethanol is produced by yeasts which were present in kefir grains, they could have inhibited metabolic activities of lactic acid and/or acetic acid producing strains, as Collar (1996) previously indicated. Accordingly, TA was lower in samples produced by innocula containing solely and/or higher amounts of kefir grains ( Table 1).…”
Section: Resultsmentioning
confidence: 85%
“…Our results for kefir samples pH and their variation are well in agreement with the study of Irigoyen et al (2005) that reported no significant change in pH of kefir samples during the storage probably due to the yeasts presence. Our findings for pH during cold storage time can be discussed by the fact that lactic acid bacteria activity decrease in the presence of yeasts (Collar, 1996) resulting in less lactic and acetic acids production. In other hands, dietary fibres such as galactooligosaccharides improve the probiotic growth without significant decrease in pH (Mei, Carey, Tosh, & Kostrzynska, 2011).…”
Section: Microbial Analysesmentioning
confidence: 75%
“…It seems lactic fermentation has been completed by the day 7. This could be explained by slower fermentation of lactic acid bacteria in the presence of yeast in kefir (Collar, 1996). Our results are in agreement with the theory suggesting a symbiotic relationship between yeast and bacteria in kefir in which they can survive and propagate by using each other's bio-products as a nutrient (Viljoen, 2001).The theory suggests that lactic acid bacteria produces galactose which can be digested by yeast which in turn can produce vitamins which boost the growth of the lactic acid bacteria.…”
Section: Microbial Analysesmentioning
confidence: 99%